Are champions different from non-champions? - Shane, Scott A. (Journal of Business Venturing, 1994)
Research on the innovation process has shown that the presence of an innovation champion—Someone who takes a personal risk to overcome organizational obstacles to innovation—is an important part of the new business development, new technology development, and organizational change processes. Champions play six valuable roles in the innovation process. They provide autonomy from the rules, procedures, and systems of the organization so that innovators can establish creative solutions to existing problems. They gather organizational support for the innovation by building coalitions between managers in different functional areas of the organization. They create loose monitoring mechanisms that allow innovators to make creative use of organizational resources. They establish mechanisms for making consensus decisions on innovations. They use informal methods to persuade other members of the organization to provide support for the innovation, and they protect the innovation team from interference by the organizational hierarchy. Some,but not all managers believe in the desirability of these championing roles.Existing research suggests that managers willing to serve as champions differ in many ways from those who are not. However, almost all of the existing research on championing has been conducted in the United States. This raises two fundamental questions: First, do champions and non-champions differ in their preferences for championing roles? Second, are these differences universal or limited to American culture? This study attempts to answer these questions by comparing the preferences for the six championing roles of individuals with championing experience and those without across 43 organizations and 68 countries. The study shows that individuals with championing experience have significantly different preferences from individuals without championing experience for five of these championing roles—building cross-functional ties, establishing autonomy from organizational norms and rules, enabling innovators to circumvent organizational hierarchy, using informal means to persuade others to support the innovation effort, and building a decision-making mechanism that includes all organization members. These differences exist after controlling for differences in the national culture of the respondents, the companies in which they work, and demographic characteristics. The results of this study suggest that differences in the preferences of champions and non-champions for the behaviors that champions adopt are consistent across cultures.